Peningkatan Kinerja Tenaga Medis Berbasis Kepuasan Kerja pada Rumah Sakit Khusus Bedah Columbia Asia Semarang - Baskoro Putra, Angga Dwi; Khajar, Ibnu (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This study aims to analyze work discipline and workload factors that influence employee performance at the Columbia Asia Special Surgical Hospital, Semarang, through job satisfaction. This research uses a quantitative research method with a purposive sampling technique, namely by distributing questionnaires with respondents who have certain criteria, namely employees of the Columbia Asia Semarang Special Surgical Hospital who are still actively working and these employees have worked for at least 2 years at the Columbia Asia Semarang Special Surgical Hospital. 145 respondents. This data analysis method uses multiple linear regression analysis techniques, with the SPSS statistical test tool, this analysis is used to measure the influence of the independent variable on the dependent variable with intervening variables.The results of this study indicate a significant positive influence between work discipline, workload, employee performance and job satisfaction. This study also proves that the job satisfaction variable plays a role in mediating the relationship between work discipline and workload variables on employee performance variables.